Student argumentation skills’ analysis on the discussion of socio-scientific issues in the concept of viruses - Yuke Mardiati; Yanti Herlanti; Alfi Lailatul Qodriyah (Universitas Islam Negeri Sumatera Utara, 2022)
This study aimed to analyze the argumentation skills of students in learning through discussion of socio-scientific issues with the concept of viruses. This research is descriptive which describes the quality of oral and written arguments. The research was conducted in class of X MIPA at SMAN Jakarta. There were 34 students involved in this study. The method of analysis to determine the pattern of arguments used is the Toulmin Analysis. The analysis of collaborative oral arguments in class used Erduran's analysis framework. Meanwhile, the quality of individual written argumentation was Dawson and Venville's analysis. The results showed that the quality of students' oral arguments reached level 5. This means that students have been able to make a claim accompanied by a warrant and rebuttal quite well. The quality of the students' written arguments reaches levels 2 and 3. This means that students' arguments consist of arguments in the form of claims (claims) accompanied by guarantors of claims (warrants) and evidence (data) and rebuttals that are still weak.. The augmentation process verbally and collaboratively in class has reached the highest level, but individually and in writing it is still at a moderate level.